MULTIPLIER EFFECT INDUSTRI PARIWISATA CANDI MUARA TAKUS TERHADAP PEREKONOMIAN MASYARAKAT DI KECAMATAN XII KOTO KAMPAR KABUPATEN KAMPAR - Muhammad Ikhsan; Mardiana '; Deny Setiawan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was carried on in Kampar regency precisely in the District XII Koto Kampar. This study was conducted in Kampar regency located in District XII Koto Kampar. This study aims to (1) Identify the characteristics of visitors, businessmen and labor (2) To identify the perception of the condition of Tourism Muara Takus by visitors, businesses and workers in the tourist area (3) Measuring multiplier effet that caused by Muara Takus tourist activities on the economy of the community. The method used is descriptive method. By sampling methods Quota sampling techniques using Sampling Insidential election. In assessing the perception of using Rating Scale and analyzing the economic impact of travel activty in Muara Takus using Keynesian Income Multiplier to see the impact directly, impact indirectly and impact advance are processed using a computer application Microsoft Excel 2010. The results of this study showed the perception of visitor 54% is good enough, the perception of buisnesses 65% good and perception of labor 66% good, For value of Keynesian income multiplier is 2.6, Income Multiplier Ratio Type I with a value of 1, and the ratio of Type II income multiplier of 1.19, in accordance with the provisions (META, 2001) if the value of Keynesian income multiplier ≥ 1 which means that the existence of Muara Takus tourism has economic impact on the economy of the local community is quite large.Keywords: Characteristics, Perception and Multiplier Effect